Gonorrhoea among China’s aging population: a 20-year nationwide analysis of epidemiological trends with 5-year projections - Peng, Rui-Rui; Chen, Zuo-Xi; Wu, Juan; Shi, Mei; Zheng, Xin; Liao, Chun-Jie; Zhu, Lin; Gong, Xiang-Dong; Long, Fu-Quan (Frontiers in Public Health, 2025)
BackgroundAdvances in longevity and pharmacological interventions have facilitated sustained sexual activity among older adults, increasing their vulnerability to sexually transmitted infections. Existing research on older adults in China has largely concentrated on HIV and syphilis, leaving critical gaps in knowledge regarding gonorrhoea.ObjectivesWe aimed to analyze trends in gonorrhoea incidence among Chinese older adults aged 60 years and above from 2004 to 2023, and to forecast infection trajectories over the next 5 years.MethodsData were sourced from the National Center for STD Control and the National Bureau of Statistics Yearbooks, standardized and stratified by gender and age groups. Temporal trend analysis utilized Joinpoint regression, and prediction model was developed utilizing an optimized Long Short-Term Memory model.ResultsWe found: (1) An overall declining yet fluctuating incidence rate (AAPC −5.84; 95% CI, −10.13 to −1.34) with three distinct phases; (2) A consistent predominance of cases among males across all age groups; (3) Slower decline rates in older age groups, particularly among those aged ≥80 years; and (4) A significant reduction in incidence rates during the COVID-19 pandemic. We projected stabilization of overall gonorrhoea incidence rates over the next 5 years (APC −3.22; 95% CI, −6.69 to 0.37), with pronounced upward trend anticipated in the ≥80 age group (APC 20.09; 95% CI, 7.71 to 33.89).ConclusionThe study highlights persistent gonorrhoea transmission risks among older adults in China, particularly the upward trajectory in the ≥80 age group. These findings call for integrating geriatric sexual health education with strengthened monitoring systems to address evolving epidemiological patterns.